Empagliflozin-associated postoperative mixed metabolic acidosis. Case report and review of pathogenesis - Sitina, Michal; Lukes, Marek; Sramek, Vladimir (BMC endocrine disorders, 2023)
BACKGROUND: Euglycemic diabetic ketoacidosis associated with SGLT2 inhibitors is a rare, relatively new and potentially fatal clinical entity, characterized by metabolic acidosis with normal or only moderately elevated glycemia. The mechanisms are not fully understood but involve increased ketogenesis and complex renal metabolic dysfunction, resulting in both ketoacidosis and hyperchloremic acidosis. We report a rare case of fatal empagliflozin-associated acidosis with profound hyperchloremia and review its pathogenesis. CASE PRESENTATION: A patient with type 2 diabetes mellitus treated with empagliflozin underwent an elective hip replacement surgery. Since day 4 after surgery, he felt generally unwell, leading to cardiac arrest on the day 5. Empagliflozin-associated euglycemic diabetic ketoacidosis with severe hyperchloremic acidosis was identified as the cause of the cardiac arrest. CONCLUSIONS: This unique case documents the possibility of severe SGLT2 inhibitor-associated mixed metabolic acidosis with a predominant hyperchloremic component. Awareness of this possibility and a high index of suspicion are crucial for correct and early diagnosis.
Keywords: SGLT2 inhibitor; Heart Arrest; srdeční zástava; Euglycemic ketoacidosis; Diabetic Ketoacidosis; acidóza; mužské pohlaví; Diabetes Mellitus, Type 2; Empagliflozin; diabetes mellitus 2. typu; Acidosis; Case report; Humans; Hyperchloremic acidosis; glifloziny; Sodium-Glucose Transporter 2 Inhibitors; lidé; Male; diabetická ketoacidóza